(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
This study uses a type of quantitative research method, which has the aim of describing the influence of interest, learning motivation on student learning outcomes in mathematics lessons on the material of Building a Flat Sided Space (BRSD). The research was conducted at SMP Negeri 6 Pati, which used a sample of 23 students in class VIII-C. In this research, the instrument used is a learning interest questionnaire (X1), a learning motivation questionnaire (X2), and a learning outcome test on the material for Building Flat Side Space (BRSD) (Y). The results showed that the correlation between learning interest (X1) and learning outcomes (Y) obtained a calculation of Tobs = 1.054, the correlation between learning motivation (X2) and learning outcomes (Y) obtained a calculation of Tobs = 1.3629, and the correlation value between interest (X1), learning motivation (X2) with learning outcomes (Y) obtained a calculation of Fobs = 0.88474, where from the calculations of the three correlations it is concluded that there is no positive and significant influence or relationship between learning interest (X1) and learning outcomes (Y), between learning motivation (X2) and learning outcomes (Y), and between interest (X1), learning motivation (X2) together with learning outcomes (Y).